2022
DOI: 10.1021/acsaelm.2c01150
|View full text |Cite
|
Sign up to set email alerts
|

Conformal Cu–CuNi Thermocouple Using Particle-Free Ink Materials

Abstract: Flexible electronic sensors are today trending toward being smaller, lighter, and also conformal, while additive manufacturing capabilities are proving crucial in their rapid prototyping. Here, we report flexible and conformal thermocouples by printing liquid metal–organic decomposition materials, consisting of Cu and CuNi particle-free conductive inks. The printed Cu–CuNi (type T) thermocouple shows a linear temperature response with a sensitivity of 20.6 μV/°C and a response time below 2 s. In addition, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The adhesion of the inkjet-printed Cu to the substrates has been a significant challenge due to the solvents, surface/liquid interactions, and sintering limitations. Researchers have tried to pretreat the ink or substrate by adding cellulose to increase the adhesion of printed Cu to the substrates . Here, the adhesion test of dry-printed Cu films to the substrate was performed according to the American Society for Testing and Materials (ASTM D3359) procedure.…”
Section: Resultsmentioning
confidence: 99%
“…The adhesion of the inkjet-printed Cu to the substrates has been a significant challenge due to the solvents, surface/liquid interactions, and sintering limitations. Researchers have tried to pretreat the ink or substrate by adding cellulose to increase the adhesion of printed Cu to the substrates . Here, the adhesion test of dry-printed Cu films to the substrate was performed according to the American Society for Testing and Materials (ASTM D3359) procedure.…”
Section: Resultsmentioning
confidence: 99%
“…Extensive studies on CuF‐AMP MOD has been done in one of our recent works. [ 42 ] Independently, nickel formate (NiF) was mixed with 1‐amino‐2‐propanol (AmIP) ligand in a molar ratio of 1:4, with subsequent centrifugation in Thinky Mixer for achieving a uniform mixture. CuF‐ and NiF‐MODs were then mixed together at a 1:1 Cu:Ni molar ratio (e.g., 3.14 g of CuF‐AMP MOD and 2.6 g NiF‐AmIP MOD) to make CuNi‐MOD.…”
Section: Methodsmentioning
confidence: 99%
“…Copper formate tetrahydrate (CuF) was mixed with aminomethyl propanol (AMP) in a 1:2 molar ratio followed by mixing at 2000 rpm for a duration of 8 min in a Thinky Mixer ARE-310. Extensive studies on CuF-AMP MOD inks were reported in our previous works . To this mixture, platinum­(II) acetylacetonate was added, with the resulting mixtures having molar ratios of 2:1, 4:1, 6:1, 8:1, and 10:1 (the left digit indicating the copper ratio and the right digit indicating the platinum ratio).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Extensive studies on CuF-AMP MOD inks were reported in our previous works. 28 To this mixture, platinum(II) acetylacetonate was added, with the resulting mixtures having molar ratios of 2:1, 4:1, 6:1, 8:1, and 10:1 (the left digit indicating the copper ratio and the right digit indicating the platinum ratio). The mixture was mixed again in the Thinky Mixer for a duration of 2 min at 2000 rpm prior to printing.…”
Section: Copper−platinum (Cu−pt) Ink Preparationmentioning
confidence: 99%